2017
DOI: 10.1016/j.colsurfa.2017.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Specific anion effects on adsorption and packing of octadecylamine hydrochloride molecules at the air/water interface

Abstract: The spread of collector molecules on bubble surfaces in salt solution is a fundamental phenomenon in the froth flotation of soluble salts, such as KCl, and consideration of ionic effects on adsorption behavior and packing of collector molecules at the air/solution interface is appropriate for study. In this work, specific anion effects on the adsorption and packing of one common collector (octadecylamine hydrochloride, ODA) at the air/water interface were investigated by employing a combination of surface pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…It agrees well with the previous study that reported that protonated amine interacts much more favorably with aromatic molecules than the neutral amine. 12,45 The marked difference in the CH range of the spectra from that of a neat ODA monolayer indicates that the indole molecules disrupted the ODA monolayer significantly, 28,46 demonstrating again the high permeability of the indole molecule into the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…It agrees well with the previous study that reported that protonated amine interacts much more favorably with aromatic molecules than the neutral amine. 12,45 The marked difference in the CH range of the spectra from that of a neat ODA monolayer indicates that the indole molecules disrupted the ODA monolayer significantly, 28,46 demonstrating again the high permeability of the indole molecule into the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The elongation of the alkyl chain further diminishes the curvature of the surfactant monomolecular film, leading to the formation of larger aggregates, indicative of heightened molecular stacking. 39,40 Generally, an increase in ethylene oxide addition increases the CMC of the surfactant and decreases the maximum adsorption capacity. However, the higher the ethylene oxide addition, the higher the surface activity efficiency of the surfactant.…”
Section: Investigation Of the Micellar Sphere-rod Transition In Aqueo...mentioning
confidence: 99%
“…MD simulations were utilized to better understand the adsorption and packing of octadecylamine hydrochloride (ODA) collector molecules at the air/ water interface in the presence of various ions in the solution. 392 Some anions (e.g., I − and SO 4 2−…”
Section: Minerals/water/gas Interfaces In Flotationmentioning
confidence: 99%
“…MD simulations were utilized to better understand the adsorption and packing of octadecylamine hydrochloride (ODA) collector molecules at the air/water interface in the presence of various ions in the solution . Some anions (e.g., I – and SO 4 2– ) are shown to penetrate the ODA monolayer at the air/water interface due to their larger size and greater polarizability and disrupt the arrangement of the ODA molecule.…”
Section: Applications Of Molecular Modeling To Froth Flotationmentioning
confidence: 99%